The Development Of The Realistic Story In Usa And Uzbek Literature And The Creation Of O. Henry - Suxrob Saitov Djumaydillayevich (Peerian Journals Publishing, 2024)
In this article, realistic examples of the genre of the story were formed in the Uzbek national process at the beginning of the 20th century. An example of this is the stories of Cho‘lpon and A. Qodiri. In the stories of a number of writers, such as G.Gulom, A.Qahhor, Sh. Kholmirzayev, O.Hoshimov, who have been blessed with this genre, one of the main criteria of the story is shortness and brevity. It can be observed that there are stories of different sizes in the works of H. Sultanov. In the stories of N. Eshonqul, the darkness of the image, the expression in deep emotional colors created harmony with the psychologism of the work.
Keywords: The Sketchbook; American Romantic Writers; English Academic Literature and